2021
DOI: 10.1016/j.heliyon.2021.e07665
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 receptor angiotensin-converting enzyme 2 (ACE2) in myalgic encephalomyelitis/chronic fatigue syndrome: A meta-analysis of public DNA methylation and gene expression data

Abstract: People with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) often report a high frequency of viral infections and flu-like symptoms during their disease course. Since this reporting is in line with different immunological abnormalities and altered gene expression profiles observed in the disease, we aimed to explore whether the expression of the human angiotensin-converting enzyme-2 (ACE2), the major cell entry receptor for SARS-CoV-2, is also altered in this neglected clinical population. In parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…We propose that similar alterations of the vascular system in response to a physical, infectious and / or emotional stressor (i.e., physiological insult) may also contribute to explain the emergence of ME/CFS. This is consistent with recent hypotheses describing vasoconstriction in muscle and brain as a principal element of ME/CFS (42)(43)(44)(45)(46), and findings of cerebral hypoperfusion (47)(48)(49) and intracranial hypertension (50) in ME/CFS patients. It is also consistent with studies that have shown that endothelial function is impaired in ME/CFS (51,52), both in large vessels and in the microcirculation (53, 54)-associated with redox imbalance (51).…”
Section: Hypoperfusion and Endotheliopathysupporting
confidence: 92%
“…We propose that similar alterations of the vascular system in response to a physical, infectious and / or emotional stressor (i.e., physiological insult) may also contribute to explain the emergence of ME/CFS. This is consistent with recent hypotheses describing vasoconstriction in muscle and brain as a principal element of ME/CFS (42)(43)(44)(45)(46), and findings of cerebral hypoperfusion (47)(48)(49) and intracranial hypertension (50) in ME/CFS patients. It is also consistent with studies that have shown that endothelial function is impaired in ME/CFS (51,52), both in large vessels and in the microcirculation (53, 54)-associated with redox imbalance (51).…”
Section: Hypoperfusion and Endotheliopathysupporting
confidence: 92%
“…While patients with ME/CFS have enhanced local responses against SARS-CoV-2, systemic responses in plasma were similar to those of HDs. In a recent study, samples from patients with ME/CFS have demonstrated altered methylation and gene expression levels for the ACE and ACE2 locus, suggesting that the patients may have a higher risk of being infected with SARS-CoV-2 ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akin to heat stroke, several new hypotheses of ME/CFS suggest that vasoconstriction and hypoxia are central to its pathology—respectively focused on the consequence of ß2 adrenergic and M3 acetylcholine receptor autoantibodies ( 41 , 42 ), a potential reduction of ACE2 expression ( 43 ), and an abnormal immune response with a concomitant impact on endothelial function ( 44 ). In addition, postural orthostatic tachycardia syndrome (POTS) is a common comorbidity of ME/CFS ( 45 ), which is a complex disorder of the vascular system also associated with gastrointestinal dysfunctions ( 46 , 47 ).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%